Highly efficient photoluminescence and lasing from hydroxide coated fully inorganic perovskite micro/nano-rods - Ying, G; Jana, A; Osokin, V; Park, Y; Taylor, RA; Farrow, T (Wiley, 2020)
The effect of surface passivation on the photoluminescence (PL) emitted by CsPbBr3 micro/nano‐rods coated with Pb(OH)2 is investigated, where a high quantum yield and excellent stability for the emission are found. The CsPbBr3/Pb(OH)2 rods generally present a peak that is blue shifted compared to that seen in rods without a hydroxide cladding at low temperatures. By increasing the temperature, it is further shown that the passivated surface states are very robust against thermal effects and that the PL peak intensity only drops by a factor of 1.5. Localized stimulated emission at defect states found within larger rods is also demonstrated, clarified by spatially resolved confocal PL mapping along the length of the rods. The diffusion parameter of the carrier density distribution is measured to be 5.70 µm for the sky‐blue emission, whereas for the defect lasing site it is found to be smaller than this excitation spot size.